THE VISCERAL FAT SIGNIFICANTLY ASSOCIATED WITH URIC ACID LEVELS AMONG THE ELDERLY AT HANA NURSING HOME - Jap, Ayleen Nathalie; Gunawan, Shirly; Firmansyah, Yohanes; Santoso, Alexander Halim (Prosiding Seminar Nasional COSMIC Kedokteran, 2025)
Visceral fat has a significant impact on metabolic health. Elevated visceral fat area could increase the risk of hyperuricemia, which may lead to further metabolic complications. The study aims to assess the relationship between uric acid levels and visceral fat accumulation and the subsequent effect on subcutaneous fat distribution in the trunk, arms, and legs among the elderly population. This study involved 61 elderly participants at Hana Nursing Home. Serum uric acid levels were measured using point-of-care testing (POCT). Body composition, including visceral and subcutaneous fat, was assessed using the Omron body composition monitor. Spearman correlation analysis evaluated the relationship between uric acid levels, visceral fat, and subcutaneous fat in different body regions, including the trunk, arms, and legs. This study has demonstrated a positive correlation between uric acid levels and visceral fat accumulation (r = 0.285, p = 0.026), subcutaneous fat in the trunk (r = 0.804, p < 0.001), arms (r = 0.752, p < 0.001), and legs (r = 0.827, p < 0.001), suggesting that having a high amount of visceral fat can be an indicator of having more subcutaneous fat as well.